ON THE COMPARATIVE CATCH EFFICIENCY OF HAND-OPERATED AND WINCH-OPERATED TRAWLS - Deshpande, S D (Indian Journal of Fisheries, 2016)
That the motorization of the indigenous fishing crafts and the introduction of modern designs of mechanized fishing boats provide the background impetus for an improvement of the existing fishing gear and methods is too well known. Some of the maritime States in India have completed the first phase of the general ’ mechanization ’ programme, namelyâ€”the installation of engines for propulsion in the existing fishing boats (Setna, 1955; Deshpande, 1958; Gurtner, 1958; Kuriyan and Balasubramanyan, 1959). The next step obviously is the introduction of modern fishing gear to increase the catch-per-unit effort and thereby to be in commensurate with the extra capital outlay. Chidambaram (1952) and John et al. (1959) review the attempts made earlier for the introduction of new gear in Indian waters.